Analysis of lncRNA and mRNA Transcriptomes Expression in Thyroid Cancer Tissues Among Patients With Exposure of Medical Occupational Radiation - Feng Shi; Ying Liu; Min Li; Peng Wen; Qiu Qin Qian; Yibin Fan; Ruixue Huang (SAGE Publishing, 2019)
Background: Occupational exposure of radiation among medical radiation workers contributes to the subsequent increased risk of thyroid cancer. Long noncoding RNAs (lncRNAs) are emerging as important regulators of cancer biology. However, little is known about lncRNA expression in thyroid cancer tissues from patients who are exposed to medical occupational radiation. The purpose of this study is to reveal the transcriptomes difference between thyroid cancer tissues and adjacent nonneoplastic thyroid tissues. Methods: Microarray technology was used in this study. Quantitative reverse transcription polymerase chain reaction was adopted to verify 6 differentially expressed lncRNAs. Gene ontology and pathway analyses were performed using standard enrichment computational methods. Potential target genes of the differentially expressed lncRNAs were predicted with 2 independent algorithms. Results: A total of 23 lncRNA and messenger RNA transcripts were found differentially expressed in the thyroid cancer tissues (fold change ≥2.0, P < .05). This differential lncRNA expression may affect many pathways, including those involved in cysteine and methionine metabolism, Huntington disease, propanoate metabolism, and carcinogenesis. Conclusions: Our study provides a transcriptome-wide screening and analysis of the lncRNA expression profile in thyroid cancer tissues from patients with medical occupational radiation exposure and lays the foundation for further investigation of lncRNAs related to thyroid cancer development and carcinogenic risk of medical occupational radiation exposure.